Applications of a novel electron energy filter combined with a hybrid-pixel direct electron detector for the analysis of functional oxides by STEM/EELS and energy-filtered imaging. (September 2022) - Ruiz Caridad, Alicia; Erni, Rolf; Vogel, Alexander; Rossell, Marta D.
Abstract: The performance and suitability of a new electron energy filter in combination with a hybrid pixel, direct electron detector for analytical (scanning) transmission electron microscopy are demonstrated using four examples. The STEM-EELS capabilities of the CEOS Energy Filtering and Imaging Device (CEFID) were tested with focus on weak signals and high spatio-temporal resolution. A multiferroic, multilayer structure of RE MnO3 ( RE = Yb, Er, Tb, Y), grown on yttria-stabilized zirconia (YSZ), is used to exemplify that this new instrumental setup produces valuable electron energy-loss spectroscopy (EELS) data at high energy losses even when using short acquisition times, providing detailed chemical information about the interfaces in this complex multilayer sample. Another functional oxide, namely a ferromagnetic La2 NiMnO6 thin film grown on SrTiO3, demonstrates that atomically resolved spectrum images can be recorded, using short dwell times and moderate beam currents in order to warrant the integrity of the sample. In a third example, inhomogeneously Er-doped YSZ shows by EELS spectrum imaging that elements at low concentrations can be detected semi-quantitatively, uncovering the expected layered Er distribution but revealing substantial interdiffusion. In a final example, we simply demonstrate that the hybrid pixel detector in combination with the energy filter can also be used for energy-filtered imaging and thus for elemental mapping complementary to EELS in scanning transmission mode. Highlights: Materials-science applications of a new electron energy filter combined with a hybrid-pixel electron detector are demonstrated. Examples of STEM-EELS and elemental mapping by energy filtered imaging (EFI) are shown. The high sensitivity of this setup enables detection elements at low concentration even at high excitation edges. Aside from the shown applications, further functionalities are planned to be implemented.